2021
DOI: 10.1155/2021/5187837
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Treatment Rules of Chronic Kidney Disease and Nursing Intervention Models of Related Mental Diseases Using Electronic Medical Records and Data Mining

Abstract: Objective. On the basis of electronic medical records, the data mining technology was adopted to explore the law of chronic kidney disease (CKD) and the intervention mode of mental health of patients. Methods. Based on the electronic medical records, the corresponding data extraction, database establishment, and data cleaning of CKD were performed. After that, the related data analysis, frequency analysis, cluster analysis, and nonparametric analysis were used to explore the laws of CKD diagnosis and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Nursing intervention is proposed based on certain physiological and pathological scientific theories, is through some corresponding scientific experiments, and can indeed help doctors give more comprehensive treatment to patients in clinical practice to a certain extent. Nursing intervention requires comprehensive consideration of many aspects such as disease, family, and psychology according to the specific circumstances of patients in clinical practice and then making the corresponding diagnosis, and the corresponding nursing staff needs sequential, targeted, and scientific nursing according to nursing guidance [3,4]. In this process, reasonable reference to the existing research results, analysis of various functional indicators of patients and expected degree of recovery, and professional clinical knowledge can achieve a good intervention effect, so as to achieve the expected results of helping the patient's physical and mental recovery, preventing complications and promoting, maintaining, or restoring the patient's physical and psychological function [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing intervention is proposed based on certain physiological and pathological scientific theories, is through some corresponding scientific experiments, and can indeed help doctors give more comprehensive treatment to patients in clinical practice to a certain extent. Nursing intervention requires comprehensive consideration of many aspects such as disease, family, and psychology according to the specific circumstances of patients in clinical practice and then making the corresponding diagnosis, and the corresponding nursing staff needs sequential, targeted, and scientific nursing according to nursing guidance [3,4]. In this process, reasonable reference to the existing research results, analysis of various functional indicators of patients and expected degree of recovery, and professional clinical knowledge can achieve a good intervention effect, so as to achieve the expected results of helping the patient's physical and mental recovery, preventing complications and promoting, maintaining, or restoring the patient's physical and psychological function [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%